Effect of Different Combinations of Gums and Emulsifiers on the Quality of Bread: Gums and Emulsifiers for Bread Quality - Haider, Muhammad Rizwan; Mueen ud din, Ghulam; Abrar, Muhammad; Mehmood, Arshad; Hussain, Ashiq; Nasir, Muhammad Umar (Biological Sciences - PJSIR, 2016)
A project was designed to evaluate the effect of different combinations of emulsifiers and gums on the quality of bread. Wheat variety AARI-11 was milled to get straight grade flour and mixed with the Emulsifiers (DMG & DATEM) and Gums (G.G & CMC) in a quantity of (0.3- 0.6 %). Both, straight grade flour as well as treated flour (combination with gums and emulsifiers) were subjected to proximate and rheological analysis. Results of the rheological study showed a significant change in water absorption, dough development time, dough stability time and dough viscosity i.e. W/A 61.33-62.93%, D.D.T 3.9- 4.8 min, D.S.T 7-9.1 min and 818.33-950.00 BU, respectively. Breads prepared with both flours were also studied for their sensory attributes during storage after the interval of 24 h. The highest score was awarded to T1 (0.3% DATEM & 0.5% guar gum) on the bases of its excellent external attributes (colour of crust, volume, symmetry of form, evenness of bake and crust character) and internal characteristics (aroma, grain, texture, taste, mastication and colour of crumb). After the sensory and physicochemical analyses, it is concluded that with the addition of DATEM (0.3%) and guar gum (0.5%) resulted in good quality of bread.